Diagnosis of tubercular lymphadenopathy by fine needle aspiration cytology and Z-N staining - Naz, Navneet; Sharma, Megha (International Journal of Research in Medical Sciences, 2019)
Background: Tuberculosis continues to be the biggest health problem in India. Tuberculosis involves respiratory, gastrointestinal tract as well as extrapulmonary site. Tubercular lymphadenopathy is the most common form of extrapulmonary tuberculosis. FNAC plays a vital role in diagnosis of tubercular lymphadenopathy. FNAC is not only used for cytological diagnosis but also used for other ancillary tests like Ziehl-Neelsen staining and AFB culture. Methods: The study was conducted in the department of pathology, Government Medical College, Jammu over a period of 6 months and included 450 cases presenting with superficial lymphadenopathy. FNAC was performed in the cases and smears in each case, were stained with May Grunwald Giemsa (MGG), Papanicolaou and Z-N stain. Results: Out of 450 cases,160 cases (35.5%) showed features of tubercular lymphadenitis. The most common site of presentation, being cervical region with 75% cases. Females outnumbered males by ratio of 1.46:1. In cytomorphology 93 cases (58.1%) showed epithelioid granulomas with caseous necrosis,37 cases (23.1%) showed caseous necrosis only while only epithelioid granulomas were seen in 30 cases (23.1%). AFB positivity was seen in 82 cases with maximum AFB positivity (78.3%) seen in cases with necrosis only. Conclusions: FNAC is a rapid diagnostic technique because of its simplicity, cost effectiveness, early availability of results and minimal invasion. FNAC is a reliable and sensitive first line investigation in diagnosis of tubercular lymphadenitis combined with AFB staining.